Recent advances in magnesium-based materials: CO₂ sequestration and utilization, mechanical properties and environmental impact - Meng, Dan (2023)
Cement industry is one of the main sources of greenhouse gases, which accounts for about 7% of global CO2 emissions. Sequestration of CO2 in cement-based materials is regarded as an effective alternative since it can convert CO2 into stable carbonates with relatively low additional energy consumption. This paper presents a comprehensive review on recent research and advances on carbon sequestration in magnesium-based binders with a focus on reactive MgO cement (RMC) and magnesium oxychloride cement (MOC). The carbon sequestration mechanism, the influence of carbonation on mechanical performance, and key parameters that control the carbonation process are summarized. In addition, a quantitative analysis of carbon sequestration in RMC-based materials is presented, demonstrating the effectiveness of offsetting carbon emissions via the use of alternative binder systems. Furthermore, a comparison of the environmental impact of Portland cement, RMC and MOC production is provided, emphasizing the need for enhancing the sustainability of cement production procedures. Overall, this paper presents a roadmap for emerging carbonation techniques that improve the mechanical performance and sustainability of magnesium-based binders.